2012
DOI: 10.1590/s1984-82502012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Programmed delivery of verapamil hydrochloride from tablet in a capsule device

Abstract: The aim of the present work was to develop a programmed drug delivery system which would be able to release the drug after 6 h of lag time by use of hydrophilic polymers. The capsule body was made impermeable by use of formaldehyde vapor treatment, while the cap was untreated. The capsule was filled with two layered tablets (tablet-in-capsule), followed by a sodium bicarbonate:citric acid mixture (SBCM) and lactose as bulking agent. Sodium alginate, chitosan, HPMC K15 and chitosan:sodium alginate complex (CSAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The observed burst releases could be explained by the fact that mannitol and lactose rapidly dissolve in water, leading to the swelling and disintegration of the tablets. Furthermore, previous studies have reported increased release rates of atenolol from HPMC matrices (Lotfipour et al, 2004), chlorhexidine digluconate from vaginal inserts (Abruzzo et al, 2013) and verapamil hydrochloride from chitosan-alginate tablets (Sah and Juyal, 2012) in the presence of NaCMC, mannitol and lactose as excipients, respectively. Despite the observed burst releases, the tablet formulation of chitosan-alginate microparticles demonstrates the potential for the delivery of xanthones to the gastrointestinal tract.…”
Section: Tablet Dissolution Test and Release Profile Of Xanthonesmentioning
confidence: 93%
“…The observed burst releases could be explained by the fact that mannitol and lactose rapidly dissolve in water, leading to the swelling and disintegration of the tablets. Furthermore, previous studies have reported increased release rates of atenolol from HPMC matrices (Lotfipour et al, 2004), chlorhexidine digluconate from vaginal inserts (Abruzzo et al, 2013) and verapamil hydrochloride from chitosan-alginate tablets (Sah and Juyal, 2012) in the presence of NaCMC, mannitol and lactose as excipients, respectively. Despite the observed burst releases, the tablet formulation of chitosan-alginate microparticles demonstrates the potential for the delivery of xanthones to the gastrointestinal tract.…”
Section: Tablet Dissolution Test and Release Profile Of Xanthonesmentioning
confidence: 93%